New art gallery holds open house (Raton, NM Raton Range, 1989)
Is about the Pocohontas Art Gallery opening.
Newspaper article
Master list item #: 133
File location is in the Raton file Cabinet
Keywords: Schadel, John -- Owner; Pocohontas Art Gallery; Art Gallery Opening; Art Exhibits; Art Displays; Raton, New Mexico